Exploring bariatric surgery. Issue 2 (March 2018) - Lockhart, Lisa; Davis, Charlotte
Abstract : Learn the basics of four common surgical options for adult obesity treatment when diet and exercise have failed to produce significant weight loss. Abstract : Learn the basics of four common surgical options for adult obesity treatment when diet and exercise have failed to produce significant weight loss.